Low-purity crude glycerin as a nutrient substitute for corn: the effect on yields of goat organs and viscera - Gomes, Rayane Nunes; Paula, Talita Almeida de; Carvalho, Francisco Fernando Ramos de; Cordeiro, Eduardo Henrique de Araújo; Nascimento, Hugo Fernando Araújo do; Mendes, Giorgio Oliveira; Oliveira, Ana Barros de; Véras, Antonia Sherlânea Chaves (Acta Scientiarum. Animal Sciences, 2020)
This study was conducted to evaluate the effects of the inclusion of low-purity crude glycerin (CG, 63.1% of glycerol) in the diets of feedlot-finished goats on the weights and yields of the non-carcass components, with are frequently used in regionals dishes (buchada and panelada). Forty castrated male goats with the initial mean body weight of 19.70 ± 2.30 kg were used. Experimental treatments consisted of inclusion of CG at levels of 0, 6, 12, and 18%, based on dry matter. The weights of the lungs, spleen, total organs (TWO), and TWO yield, as a function of the slaughter body weight, decreased linearly. It was shown that the rumen portion of the weight showed a quadratic effect, at the level of 10.71% of CG, with a minimum point of 0.37 kg. Similar behavior was observed for the reticulum, with a minimum point of 0.08 kg, at the level of 7.5% of CG. The weights and yields of the buchada and panelada were negatively influenced by the experimental diets. Low-purity crude glycerin may partially replace corn and be included in up to 6% of the dry matter of the finished goats’ feedlot diet without adversely affecting weights and yields of organs, viscera, and regional dishes, such as buchada and panelada.